Problem behaviour as a secondary consequence of learning disability and the possibility of support pupil by the class teacher - Zemančíková, Vladimíra (e-Pedagogium, 2022)
The paper deals with the issue of problem behaviour of pupils as a secondary consequence of learning disabilities and at the same time with the possibilities of their support by class teachers. It presents the results of research conducted through content analysis of textual documents, namely the pedagogical characteristics of pupils with learning disabilities, which include the Conners' Teacher Rating Scale. The data were processed through the statistical program SPSS. The aim was to determine the form and degree of occurrence of manifestations of problem behaviour in pupils with developmental learning disabilities, also with regard to their work effort and the quality of parental cooperation with the school. Based on the identified externalizing and internalizing manifestations of problem behaviour, the text concludes with recommendations for class teacher support for students with learning disabilities.
Keywords: problem behaviour; specific developmental learning disability; class teacher.